Keeping the Goal in Sight: Testing the Influence of Narrowed Visual Attention on Physical Activity. (March 2020) - Balcetis, Emily; Riccio, Matthew T.; Duncan, Dustin T.; Cole, Shana
Rates of physical inactivity continue to rise in the United States. With this work, we tested the efficacy of a strategy affecting the scope of visual attention designed to promote walking as a form of exercise. Specifically, we examined the influence of narrowed attention on the frequency (Studies 1a, 1b, and 3) and efficiency (Studies 2 and 4) of physical activity in general (Studies 1 and 2) and within exercise bouts measured across multiple days (Studies 3 and 4). We provide convergent evidence by investigating both individual differences in (Studies 1 and 2) and experimentally manipulated patterns of visual attention orienting (Studies 3 and 4). We discuss implications of attentional strategies for self-regulation and fitness.